A lignan with glucose uptake activity in 3T3-L1 adipocytes from the stem bark of Knema patentinervia - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Md. Jaffri, Juliana; Amri, Mohamad Shahreen; Darnis, Deny Susanti; Abd Hamid, Shafida; Rezali, Mohd Fazlin; Mahmood Hasan, Choudhury; W Read, Roger; Ahmed, Qamar Uddin; Ahmad, Farediah (Faculty of Pharmacy, University of Karachi, 2017)
A new naturally occurring dibenzylbutyrolactone lignan named isocubebinic ether has been isolated from Knema patentinervia. The structure was established by spectroscopic methods, which include Ultraviolet, Infrared, Nuclear Magnetic Resonance and Mass Spectrometry. The compound showed activity in the stimulation of glucose uptake by 3T3-L1 adipocytes.